2021
DOI: 10.2196/25307
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Assisted Home Care for People With Dementia and Their Relatives: Scoping Review

Abstract: Background Assistive technologies for people with dementia and their relatives have the potential to ensure, improve, and facilitate home care and thereby enhance the health of the people caring or being cared for. The number and diversity of technologies and research have continuously increased over the past few decades. As a result, the research field has become complex. Objective The goal of this scoping review was to provide an overview of the resea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…To avoid a tendency for technological solutionism [ 50 ], considering that the implementation and appropriation of technologies are synonyms, it seems essential to finely define the implications and entanglements and identify the contributions and limitations of digital solutions used to maintain or develop social ties. This aim can be achieved through an increased number of studies based on empirical methods [ 51 ]. Indeed, previous studies on long-term care facility residents’ remote social ties have used standardized scales, such as the Geriatric Depression Scale [ 10 ], combined with loneliness and social support behavior scales [ 11 ] or with loneliness and quality of life scales [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid a tendency for technological solutionism [ 50 ], considering that the implementation and appropriation of technologies are synonyms, it seems essential to finely define the implications and entanglements and identify the contributions and limitations of digital solutions used to maintain or develop social ties. This aim can be achieved through an increased number of studies based on empirical methods [ 51 ]. Indeed, previous studies on long-term care facility residents’ remote social ties have used standardized scales, such as the Geriatric Depression Scale [ 10 ], combined with loneliness and social support behavior scales [ 11 ] or with loneliness and quality of life scales [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies considered the perspective of the residents, as previous research has stated. The need for well-developed and tested interventions was indeed highlighted by Palmdorf et al [ 51 ], who showed that there is a lack of information about the actual needs of the users of digital technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The focus group findings highlight the complex and dynamic implications of providing care for persons living with dementia in their homes. More importantly, this study contributes to the growing literature on how technology can support care for people with dementia living in the community [ 18 , 19 ] and the importance of a user-centered design approach [ 20 ]. Overall, the stakeholder group participants share a widespread belief about the benefits of technology in general and about the Generation Connect platform, specifically with regard to the platform’s support efforts for caring for individuals with dementia in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Technology‐assisted interventions can be used to bridge communication, reduce burden, improve health outcomes, and manage the costs in dementia care (Hirt et al, 2019; Palmdorf et al, 2021), expanding the ability to provide remote services to monitor, enhance, and enable home care, improving the health and well‐being of both caregivers and patients (Greenhalgh et al, 2015; Palmdorf et al, 2021; Welch et al, 2021). Technology‐assisted interventions refer to any treatment that employs technology as a mediating factor to create, produce, or offer health promotion materials and practices (Wang, Fadhil, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only one systematic review and meta‐analysis has examined the outcomes of technology‐assisted interventions in people with dementia, which found that these interventions can successfully decrease risky behaviors (Brims & Oliver, 2019). The results of the two prior scoping reviews showed improved safety for persons with dementia (Budak et al, 2021; Palmdorf et al, 2021). No systematic review or meta‐analysis has yet been reported examining the efficacy of technology‐assisted interventions on physical or psychological functional outcomes in the population of individuals with dementia.…”
Section: Introductionmentioning
confidence: 99%